Sosialisasi Kegiatan Webinar: Kenali Bahaya Penyalahgunaan Obat Sedatif Sejak Dini - Herman Widjaja; Aryanilo Aryanilo; Adylla Adawiyah Haryana; Junaida Pramesti; Mario Parningotan Hutapea; Susana Jelita Lestari Tandang; Pida Khaerunisa; Raditha Dellafanny; Fulgencia Maria Amelia De Jesus Soares; Winda Novaliani (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Sedative drug abuse remains a public health issue that can lead to dependency, cognitive impairment, respiratory problems, and various adverse social consequences. Limited public knowledge particularly among university students regarding the safe use of sedative drugs is a factor that increases the risk of abuse. This activity aimed to raise participant knowledge and awareness regarding the dangers of sedative drug abuse from an early stage. An educational webinar conducted via Zoom served as the method, involving 20 participants comprising university students and the general public. The material was delivered through presentations, interactive discussions, and Q&A sessions. Evaluation was conducted using pre-test and post-test methods to measure participants' level of understanding following the webinar. Results showed that all participants completed the activity and submitted the post-test. Participants demonstrated a high level of knowledge after the webinar, with correct answer rates ranging from 70% to 100% across all indicators. The highest level of understanding was observed regarding examples of benzodiazepine drugs (100% correct answers), while the lowest was regarding the sedative class with the highest risk of dependency (70% correct answers). Overall, there was an increase in participant knowledge, with an average understanding level of 85%. Participants responded positively to the material and actively engaged in the discussion and Q&A sessions. The tangible impact of this activity was heightened participant awareness regarding the dangers of sedative drug abuse and the importance of using medication according to healthcare professionals' recommendations, thereby helping to prevent drug abuse among students and the general public.